Docentes com deficiência na educação superior brasileira e condições de trabalho - Ferreira, Sally Cristina Gouveia da Silva (Universidade Federal de São Carlos, 2024)
This work is an analysis of the working conditions of teachers with disability in Brazilian public universities. Its general objective is to: Analyze the working conditions of teachers with disabilities who work in public Higher Education Brazilian. And as specific objectives: explore the teachers’ workday with disability, identify how your routine and the development of your work in the institution and verify the family's participation in the trajectory of the teacher with a disability. In its methodology included the interview procedure of five university professors with disabilities, from the southeast, north, center-west and northeast Brazilian regions, four of which participants at the federal and one state level. The results revealed that teachers face architectural and attitudinal barriers in their work, that their working day is exhaustive and that her family was an important support during her professional career, she helped and supported the work to be carried out, contributing, in some cases, to the teacher's permanence in his work. The data from this research indicated that the concrete working conditions of the university professors interviewed, included accumulation of several functions, a fact identified as harmful to their health, in addition to the environment of work has been identified as not facilitating the development of work with excellence.
Teachers with disabilities in higher education brazilian and working conditions
Keywords: Educação especial; Professores com deficiência; Trabalho; Trajetória; Special education; Teachers with disabilities; Work; Trajectory; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL